Titles: The Emerging Priority in Bringing Bibliographic Control to Social Science Machine-Readable Data Files [MRDF] - Sue A. Dodd (IASSIST Quarterly, 1978)
Titles: The Emerging Priority in Bringing Bibliographic Control to Social Science Machine-Readable Data Files [MRDF]